2021
DOI: 10.1002/tpg2.20145
|View full text |Cite
|
Sign up to set email alerts
|

QTL for seed shattering and threshability in intermediate wheatgrass align closely with well‐studied orthologs from wheat, barley, and rice

Abstract: Mention of trade names or commercial products in this publication is solely for the purpose of providing specific information and does not imply recommendation or endorsement by the U.S. Department of Agriculture. USDA is an equal opportunity provider and employer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Shattering was rated on a scale of 0 to 5, where 0 indicated no shattering and 5 indicated more than 12 florets shattering per evaluated spike (DeHaan et al, 2018). From 2016 to 2018, shattering was considered a single trait; however, work by Altendorf (2021b) indicated that floret and brittle rachis shattering should be scored separately, so beginning in 2019 brittle rachis was scored as a separate trait in the IWG population. In addition, many other secondary traits including seeds spike −1 , spikelets spike −1 , florets spike −1 , and FSU were evaluated.…”
Section: Phenotypic Assessmentmentioning
confidence: 99%
“…Shattering was rated on a scale of 0 to 5, where 0 indicated no shattering and 5 indicated more than 12 florets shattering per evaluated spike (DeHaan et al, 2018). From 2016 to 2018, shattering was considered a single trait; however, work by Altendorf (2021b) indicated that floret and brittle rachis shattering should be scored separately, so beginning in 2019 brittle rachis was scored as a separate trait in the IWG population. In addition, many other secondary traits including seeds spike −1 , spikelets spike −1 , florets spike −1 , and FSU were evaluated.…”
Section: Phenotypic Assessmentmentioning
confidence: 99%
“…(2019) also identified QTL for multiple traits on chromosome 5 including stem length, and seed nakednesss (threshing ability). In our previous work in this NAM population, chromosome 5 housed QTL for threshing ability, shattering, and brittle rachis (Altendorf et al., 2021c). On chromosome 9, Larson et al.…”
Section: Discussionmentioning
confidence: 86%
“…As genomic selection becomes increasingly routine in the domestication of IWG (Crain et al., 2020a), additional markers for important component traits will be useful. The IWG NAM population has proven to be an effective resource for identifying new QTL, previously identified QTL, and QTL that align closely with known orthologs from other species (Altendorf et al., 2021a, 2021c). Here we applied the IWG NAM population to the analysis of a series of 11 component traits with varying direct and indirect effects on yield (Altendorf et al., 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations